EVALUASI HASIL INVESTIGASI KONTAK SERUMAH PADA PASIEN TUBERKULOSIS DI KOTA MEDAN - MAULIDA SHAFI; ISTI ILMIATI FUJIATI; ELMAN BOY; DES SURYANI (JURNAL ILMIAH SIMANTEK, 2021)
This study aims to determine the distribution of TB suspects based on demographics, symptoms, and risk factors and therelationship between household contact with TB suspects. This study used a descriptive method with cross sectional design.Data were processed using SPSS Chi-Square test. The results showed that the frequency of TB suspects in people whocontact with TB patients by age was at the age of 21-40 years, based on gender the most frequency was found in males 41people (62.1%). Based on symptoms obtained frequency the most common symptom was cough (89.4%), based on the riskfactor for the most frequency in smokers (19.7%), and based on the relationship of household contact with suspected TBusing the Chi-square statistical test showed that the probability value (p) <0.05 (p = .000). This means that at the 95%significance level with ɑ = 0.05, there is a significant relationship between household contact with TB patients with suspectedTB. From the results of the study it was found that the frequency of TB suspicion among people who had household contactwith TB patients based on age at most was in the age group of 21-40 years totaling 19 patients (28.8%).